2018
DOI: 10.1007/s00213-018-5000-y
|View full text |Cite
|
Sign up to set email alerts
|

A cFos activation map of remote fear memory attenuation

Abstract: These results suggest that progressive fear attenuation mediated by repetitive exposure is accompanied by sustained neuronal activation and not reverted to a pre-conditioning brain state. These findings contribute to the identification of brain areas as targets for therapeutic approaches against traumatic memories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
75
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 66 publications
14
75
2
Order By: Relevance
“…The lack of group differences during conditioning also suggests that there were no intrinsic effects of the hM4Di virus in the absence of CNO. We then replicated previous work showing that with the passage of time, fear memories are processed to a lesser extent within the HPC and rely on neocortical storage (Teixeira et al, 2006;Lesburgueres et al, 2011;Silva et al, 2018;DeNardo et al, 2019). When fear memory recall following conditioning was tested after 1 d, we observed a more pronounced recruitment of cellular activity compared to the PL.…”
Section: Discussionsupporting
confidence: 87%
“…The lack of group differences during conditioning also suggests that there were no intrinsic effects of the hM4Di virus in the absence of CNO. We then replicated previous work showing that with the passage of time, fear memories are processed to a lesser extent within the HPC and rely on neocortical storage (Teixeira et al, 2006;Lesburgueres et al, 2011;Silva et al, 2018;DeNardo et al, 2019). When fear memory recall following conditioning was tested after 1 d, we observed a more pronounced recruitment of cellular activity compared to the PL.…”
Section: Discussionsupporting
confidence: 87%
“…Although we examined the underlying mechanism of fear memory in cerebellar cortex, PCspecific STAT3 deletion may have a more widespread impact on the brain's fear memory 13 network in general. Previous studies have shown that removal of only a few highly interconnected areas (high-degree nodes) of the fear network was enough to disrupt fear memory consolidation (Vetere et al, 2017, Silva et al, 2019. Under this assumption, we performed immunohistochemistry for detecting c-fos expressions in the brain after auditory long-term fear memory retrieval tests.…”
Section: Increased Neural Activity Of Fear-related Regions In the Stamentioning
confidence: 99%
“…This prediction based on anatomical connectivity is supported by transient neuronal synchronization across these structures and functional studies showing that inactivation of the RE affects especially those behaviors, which depend on prefrontal–hippocampal communication, such as spatial working memory and long‐term spatial and contextual memory consolidation (Ali et al, ; Barker & Warburton, ; Ferraris et al, ; Griffin, ; Hallock, Wang, & Griffin, ; Hembrook & Mair, ; Hembrook, Onos, & Mair, ; Roy, Svensson, Mazeh, & Kocsis, ; Vetere et al, ; Xu & Sudhof, ). In addition, the RE has been implicated in attention, behavioral flexibility and impulse control but also more basic functions such as circadian regulation, nociception and fear (see Cassel et al, for review; Prasad, Macgregor, & Chudasama, ; Silva, Burns, & Graff, ; Vetere et al, ).…”
Section: Introductionmentioning
confidence: 99%